CLINICAL FEATURES OF THE COURSE OF ACUTE MYOCARDIAL INFARCTION IN INDIVIDUALS OF WORKING AGE AGAINST THE BACKGROUND OF INTACT CORONARY ARTERIES (Clinical case) - Khasanjanova Farida Odylovna (Scholar Express Journals, 2025)
This scientific paper presents a clinical case of acute myocardial infarction (AMI) in a patient of working age. This study was conducted at the Samarkand Regional Branch of the Republican Specialized Scientific and Practical Medical Center of Cardiology (SRN RSNPMC). The object of the study was a 44-year-old patient with AMI. During percutaneous coronary intervention (PCI), coronary angiography did not reveal changes in the coronary arteries. Echocardiography revealed changes in local contractility, without impairment of global contractility. Taking into account the nature of changes in the level of cardiospecific enzymes, ECG dynamics, the final diagnosis was: Ischemic heart disease. Non-transmural myocardial infarction with ST segment elevation with transient (thrombotic) occlusion of the left coronary artery, anterior septal wall with the apex capture.
Keywords: acute myocardial infarction; coronary artery; working age